Association of Comedication Quality With Chemotherapy-Related Adverse Drug Reactions and Survival in Older Colorectal Cancer Patients. Issue 5 (12th July 2021) - Chen, Li-Ju; Nguyen, Thi Ngoc Mai; Laetsch, Dana Clarissa; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann; Schöttker, Ben
Abstract: Background: Evidence about the clinical relevance of appropriate comedication among older colorectal cancer (CRC) patients is sparse. Methods: A cohort study was conducted with 3239 CRC patients aged 65 years and older. To assess comedication quality, we calculated the total Fit fOR The Aged (FORTA) score and its subscores for medication overuse, underuse, and potentially inappropriate medication use. Multivariable Cox proportional hazards or logistic regression models were performed to evaluate the association of comedication quality with up to 5-year overall survival, CRC-specific survival, and chemotherapy-related adverse drug reactions. Results: Overall, 3239 and 1209 participants were included in analyses on survival and adverse drug reactions, respectively. The hazard ratios [95% confidence intervals] for the total FORTA score ≥ 7 versus 0–1 points were 1.83 [1.40–2.40] and 1.76 [1.22–2.52] for up to 5-year overall and CRC-specific survival, respectively. Worse up to 5-year overall survival and CRC-specific survival was also evident for FORTA subscores for potentially inappropriate medication use and overuse, whereas no association was observed for underuse. Although results for the total FORTA and potentially inappropriate medication score were much stronger among patients receiving chemotherapy, no significant associations with chemotherapy-related adverse drug reactions were observed. Moreover, associations were particularly strong among men and rectal cancer patients as compared to women and colon cancer patients. Conclusions: Poor total comedication quality was significantly associated with worse up to 5-year overall and CRC-specific survival. Randomized controlled trials are needed to test whether improved cancer comedication management in older CRC patients prolongs survival.